A study on behavior towards retirement planning at Majlis Perbandaran Sungai Petani, Kedah / Jamaluddin Ibrahim and Muhammad Saufie Mohamad Nadzri - Ibrahim, Jamaluddin; Mohamad Nadzri, Muhammad Saufie (2018)
The purpose of the study is to identify factors influencing behaviour towards retirement planning at Majlis Perbandaran Sungai Petani, Kedah. There is issue regarding retirement planning such as the employee do not do a good job of investing the meager retirement funds that employee have scrapped together. The data collected using the quantitative method by distributed questionnaire. First, this study is conducted by focusing on staff of Majlis Perbandaran Sungai Petani, Kedah. The number respondents are 226 for the survey questionnaire using the formula table sample size population proposed by Sekaran and Bougie (2003). The methodologies used are descriptive statistics analysis, correlation and multiple regression using for test analysis. The result from analysis show three independent variable which influence the dependent variable which are retirement planning. Those factors are knowledge, attitude and awareness that will influence the behaviour towards retirement planning. The result of this study shows the most dominants factors is knowledge that influencing the behavior towards retirement planning at Majlis Perbandaran Sungai Petani.